Entrapment of the Fifth Lumbar Spinal Nerve by Advanced Osteophytic Changes of the Lumbosacral Zygapophyseal Joint: A Case Report - Ohnishi, Yu-ichiro (Korean Society of Spine Surgery, 2012)
A 54-year-old female patient had a 6-year history of backache and left sciatica. Five years earlier, she had undergone surgery in another hospital for left L4-5 disc herniation. Computed tomography revealed the ossified wall that enclosed the left L5 nerve root. There were also osteophytic changes in the left L5-S zygapophyseal joint. These osteophytes developed rostrally, along the left L5 nerve root, throug h the intervertebral foramina. We performed decompression surgery for the left L5 nerve root, and surgery resulted in symptomatic relief. We experienced a rare clinical presentation of osteophytic formation, with a specific configuration in relation to the nerve root. Surgeons should be aware of entrapment of the lumbar spinal nerve by advanced osteophytic changes occurring in the zygapophyseal joint after lumbar surgery.